Pertumbuhan Plantlet Anggrek Vanda tricolor Lindl. secara In Vitro dengan Penambahan Bubur Ubi Kayu pada Media MS - IDA AYU PUTRI DARMAWATI; HESTIN YUSWANTI (Fakultas Pertanian Universitas Udayana, 2014)
Growth of Plantlets of Vanda tricolor Orchid In-Vitro on the Cassava Pulp-Enriched MS Medium.Addition of organic matter into the culture medium is commonly used for increasing the source of sugar, vitamins and amino acids. The aim of this study was to determine the effect of the cassava pulp on the growth of Vanda tricolor plantlet, and to investigate appropriate dose for the optimal growth of plantlets. The experiment utilised a Randomized Completely Design with six treatments i.e. UO (MS medium without any organic matter), U1 (MS medium + 35 g/L cassava pulp), U2 (MS medium + 40 g/L cassava pulp), U3 (MS medium + 45 g/L cassava pulp), U4 (MS medium + 50 g/L cassava pulp), and U5 (MS medium + 45 g/L cassava pulp) with five replicates. The result showed that addition of cassava pulp significantly increased number of leaf, number of root and dry weight of plantlets. The highest number of root (i.e. 5.8) was obtained with addition of 50 g/L cassava pulp, while the highest dry weight of plantlet (i.e. 0.28 g) was on addition of 55 g/L cassava pulp.